Crystal structure and luminescence properties of a novel single-phase orange-red emitting phosphor Ca9La (PO4)7:Sm3+. Issue 26 (17th April 2018) - Ma, Bin; Ma, Xiaoqin; Xu, Tonghui; Su, Ke; Zhang, Qianxin
Abstract : Ca9 La1 –x (PO4 )7 : x Sm 3+ phosphors (0.01 < x < 0.25) were successfully synthesized. Crystal structure and luminescence properties of the phosphors were discussed in detail. Abstract : Ca9 La1− x (PO4 )7 : x Sm 3+ phosphors (0.01 < x < 0.25) were synthesized via high temperature solid-state reaction. Their properties including crystal structure, decay performance, thermal stability and photoluminescence were examined in detail. Phase analysis indicated that the phosphors crystallized in a rhombohedral structure, and the emission spectra of the phosphors consisted of four peaks centered around 570, 607, 653, and 714 nm, attributed to Sm 3+ ions transitions 4 G5/2 → 6 HJ ( J = 5/2, 7/2, 9/2, and 11/2, respectively). The optimal Sm 3+ doping content was 0.12 mol and the Ca9 La(PO4 )7 :Sm 3+ phosphor also exhibited better thermal stability compared to other phosphors. In addition, the mechanism behind the energy transfer between Sm 3+ ions was determined to be dipole–dipole interactions as described by Dexter theory. The results indicated that as orange-red phosphors, Ca9 La (PO4 )7 :Sm 3+ phosphors were promising candidates for being integrated into white light emitting diodes.